New species of Pseudochromadora Daday, 1899 (Nematoda: Desmodoridae) from Russky Island (the Sea of Japan) - Mordukhovich V.V., Fadeeva N.P., Semenchenko A.A., Zograf J.K (Russian Journal of Nematology, 2015)
Pseudochromadora rossica sp. n. is described from shallow subtidal muddy sediments in Russky Island (the Sea of Japan). Pseudochromadora rossica sp. n. differs from other species of the genus through the combination of the following characters: the position of cephalic setae; the position of amphids and sexual dimorphism in the shape of the fovea amphidialis (loop-shaped in males, unispiral in females); six longitudinal rows of somatic setae; the presence of interdigitation of body annuli at level of lateral alae; no precloacal supplements; cephalic capsule with rounded labial region; buccal cavity with a large dorsal tooth and two small ventrosublateral teeth; and absence of spines on the cuticle. The sequences of D2-D3 region of the 28S rDNA are provided for identification based on the DNA analysis.